O direito na filosofia de Slavoj i ek: perspectivas para o pensamento jurídico crítico - Grillo, Marcelo Gomes Franco (2009)
The present search has as object the right in the slovenian philosopher Slajov i ek´s work. The philosophy of the right is looked for in that author, considering its proximity as the legal marxism and with the critical philosophies. Therefore will be possible two verifications of the right in Zizek: one related to the legal Marxism and other, without being it, but still yes, in general, critical. For the first slope, the Marxist, there is the possibility of a subdivision. i ek has two apprehensions of the legal Marxism. One is more literal to Marx's work, in the comparison with the legal Marxism of Pachukanis, and other, without being similar to the first one, composed by a Marxist critical reading of the democracy, of the capitalism, of the citizenship and of the themes of the minorities and of the environment, as well as a theorise of the psychoanalysis, as it was already done before by the authors of the school of Frankfurt, however being used of Lacan and not of Freud. Specifically for the subjects of the democracy and of the i ek´s citizenship, sometimes, implicitly enters into contradiction with the vision most radical of pachukanis. In order to reinterpret the Marxist theory, the Slovenian author proceeds an analysis of the contemporary society, based in their current problems and with examples of the politics. There is still the possibility of an approach of the theory of pachukanis´s right with the social psychoanalysis starting from the Slovenian author's writings, basing on the previous propositions of Lacan. Regarding to the second slope, the critic Non Marxist, to clarify it, has the development by the author of Lubliana of the themes of the human rights, of the citizenship (the critic of the neoliberalism) and of the possible historical readings of the legal positivism and of the philosophy of right´s Hegel, as well as of the critic of the right being used of a critical assimilation of the "philosophy of right of the exception", of Carl Schmitt, among others, what approximates i ek of the philosophy of the power. On the other hand, the acceptable approach of the exception as the rupture bearing for the revolution will place i ek as an author Post-Marxist.